PEMIKIRAN PENDIDIKAN PERSPEKTIF FILSUF MUSLIM Kajian Kritis terhadap Pemikiran Muhammad Abduh dan Muhammad Iqbal) - Hasan Baharun (Universitas Nurul Jadid, 2016)
The role of philosophy in the development of Islamic education has a very important, especially in determining the direction of education in accordance with the expectations of all parties. Muhammad Abduh and Muhammad Iqbal was a leading figure of Muslim philosophers who provide brilliant ideas for the direction of educational reform Islam. Through the concept of renewal that has been overshadowed in the analysis of the social context of religious and educational experience of the two leading figures, make education easily accepted thinking and developed in some parts of the world so that it becomes the treasury for the development of Islam in the world. According to him, education is a primary need of man, so it is necessary to look for alternative solutions in order to get out of the intellectual stagnation of Muslims at the time. Both strive to transform education thought the Muslims of his time in order to learn from the empirical reality and are not confined to the rigidity and stagnation due to rampant blind imitation, heresy, zuhd, and superstition which binds the Muslims of his time. Both saw that the main cause of backwardness of Muslims is quite alarming is the loss of intellectual traditions, namely freedom of thought.